Pengaruh Brand Ambassador dan Kualitas Produk terhadap Keputusan Pembelian dengan Citra Merek pada Shampo Clear di Kota Medan - Hasanah, Viola Nurul; Suryani, Wan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the influence of brand ambassadors, product quality, and brand image on purchase decisions, as well as to examine the impact of brand ambassadors and product quality on brand image. In addition, the study explores the mediating role of brand image in the relationship between brand ambassador and product quality on purchase decisions among consumers of Clear Shampoo in Medan City. The population of this study consists of Medan City residents who have purchased Clear Shampoo, with a total sample of 100 respondents. Data collection was conducted through the distribution of questionnaires, and data analysis was performed using the Partial Least Squares (PLS) method with the SmartPLS software. The coefficient of determination (R²) shows that brand ambassador and product quality variables explain 61.5% of the variance in brand image, while brand ambassador, product quality, and brand image collectively explain 64.7% of the variance in purchase decisions. Thus, it can be concluded that brand ambassador, product quality, and brand image play a significant role in influencing consumer purchase decisions for Clear Shampoo products.